Synthesis And Characterization Of Titanium Dioxide Nanotubes For Sonocatalytic Degradation Of Organic Dyes In Wastewater - Pang, Yean Ling (2013)
The sonocatalytic degradation of Rhodamine B was studied using titanium dioxide nanotubes (TiO2 NTs) with various annealing temperatures ranging from 300 oC to 900 oC for 2 h. Characterizations of the catalysts were performed using SEM, TEM, EDX, EA, AAS, XRD, Raman spectroscopy, FT-IR, nitrogen adsorption-desorption, UV-vis DRS, TGA-DTA, zeta potential measurement and XPS. The effect of catalytic activity for TiO2 nanoparticles (NPs) or various annealed TiO2 NTs and various experimental parameters including the use of various organic dyes (Congo Red, Reactive Blue 4, Methyl Orange, Methylene Blue and Rhodamine B), initial concentration of Rhodamine B of 50−150 mg/L, catalyst dosage of 0.5−2.5 g/L, solution pH of 1−11, ultrasonic frequency of 35 or 130 kHz, ultrasonic power of 20−100 W, hydrogen peroxide (H2O2) dosage of 4−20 mM, solution temperature of 25−50 oC and the presence of dissolved air at 1 L/min were examined to determine the optimum conditions. The optimum conditions for sonocatalytic degradation of Rhodamine B (88.47 % after 2 h) occurred when the initial concentration of the dye was 50 mg/L, 2 g/L of TiO2 NTs-300, solution pH of 7, ultrasonic power of 50 W, ultrasonic frequency of 35 kHz and H2O2 dosage was 8 mM at 45 oC ± 2. The as-prepared TiO2 NTs was modified by introducing urea on TiO2 NTs at molar ratios of N: Ti between 0.1–1.0. Urea doping at N: Ti equals to 0.3 led to an increment in the sonocatalytic degradation of Rhodamine B up to 86.75 % after 1 h. Meanwhile, Fe-doped TiO2 NTs at molar ratios of Fe: Ti between 0.001−0.02 were prepared. Fe doping at Fe: Ti equals to 0.005 gave the highest sonocatalytic activity (91.19 %) after 1 h.